Pemanfaatan teknologi mesin pada proses produksi kopi mengkudu UKM wasiah herbal Probolinggo - Trismawati, Trismawati; Puspitarini, Renny Candradewi; Maksin, Mastina; Basit, Abdul (Abdimas Siliwangi, 2024)
Noni fruit is one of the fruits that is looked down upon by the general public. Many noni fruit plants are allowed to grow wild, unkempt and noni fruit is also left to fall on plantations, yards and roadsides. In fact, noni fruit has extraordinary benefits such as curing stomach acid, cholesterol, high blood pressure (hypertension), gout, ulcers, cancer tumors and increasing stamina. This potential is not wasted by the target partner (UKM Wasiah Herbal) to process noni fruit into high-quality noni coffee powder. Various problems arise in the production process caused by very limited resources and capital. The assistance from the government through the manufacture of oven machines and roasting machines is able to simplify the production process very effectively. By using oven machines and roasting machines, UKM Wasiah Herbal produces noni coffee powder that has a high selling value. Both machines are able to cut long times and high costs, especially in the drying and roasting processes that previously used solar power and traditional tools. Both machines have also been tested before being handed over to the target partner. The trial results show that the effectiveness of the noni coffee production process is very fast, efficient and produces very satisfactory production for partners.